Political Behavior of Beginner Voters in the 2020 Gowa District Regional Election in Paccinongang Village, Somba Opu District - Said Ahmad, M Ridwan; Arifin, Zainal; Putra Agustang, A Dody May (KnE Social Sciences, 2024)
This study aims to determine the political behavior of beginner voters in the 2020 Gowa Regency regional election in Kel. Paccinongang Kec. Somba Opu. The subjects in this study were beginner voters including: (1) novice voters, namely adolescents aged 18 years and participating in the 2020 regional elections for the beginner, (2) reports of agencies related to this study. This study selects informants purposively. By using descriptive qualitative analysis. The results showed that: 1. the behavior of beginner voters is very dominant using sociological approaches in making their choices. Beginner voters choose candidates for the regional head, namely the regent and deputy regent of Gowa Regency by emphasizing demographic and socioeconomic backgrounds. The psychological approach is very minimal because this approach depends on the performance of political parties, and how to attract beginner voters. In addition to these two approaches, the rational choice approach places beginner voters making their choices with the tendency to choose candidates for Regent and Vice Regent by looking at their personal needs, namely the needs of their own families, it can be seen that they choose because they are based on the vision and mission of the candidate to help their lives. 2. Supporting factors are encouragement from parents, certain figures, and peers. In addition, the vision and mission of the candidates can encourage the interest of beginner voters. Inhibiting factors: it is the number of hoax news such as defamation and pitting both parties that makes beginner voters end to be very difficult to make their choice. Keywords: political behavior, beginner voters